(untitled) (CIPEEX, 2025)
The strength of the muscles in the lumbar region plays an important role in daily health and well-being. Establishing reference values for lumbar muscle dynamometry in adults helps improve the understanding of this body region and ensures that diagnoses and treatments are more accurate. The study on Reference Values for Dynamometry aims to establish standards for lumbar muscle strength levels, considering variations by age and sex. The methodology involves an integrative review of the literature on reference values for lumbar dynamometry in adults. The research was conducted using databases such as PubMed, CAPES Journals, and the Virtual Health Library (BVS), using the descriptors “Lumbar Region,” “Dynamometry,” “Muscle Strength,” and “Adult.” Articles published in the last 10 years were selected, focusing on the analysis of methodology, study population, and results related to lumbar muscle strength. The search yielded 10 documents—2 in BVS, 0 in PubMed, and 8 in CAPES Journals. After reviewing titles, descriptors, and abstracts, 9 documents were excluded for not aligning with the research objective, leaving 1. The study included 691 healthy adults (382 men and 309 women) from Joinville, SC, aged 18 to 45 years. Lumbar strength was assessed using a CZ FLEXAR®️ dynamometer. Men showed an average strength of 114.00 kgf (±24.50), while women averaged 48.50 kgf (±18.80). The results showed significantly higher lumbar strength in men. Additionally, it was observed that muscle strength varies according to age, physical activity, and sociodemographic factors, highlighting the need to consider these variables when interpreting results and applying the values to different regions of Brazil. This study on lumbar dynamometry in adults demonstrated a scarcity of research in the literature. The findings revealed that men have significantly greater lumbar strength than women, consistent with patterns found in other studies.